Examining lifestyle factors as potential moderators of the link between childhood adversity and comorbid psychological distress and obesity in early adulthood - Tom Woofenden; Graeme Fairchild; Thomas Matthew Lancaster (BMC Public Health)
Abstract Background Whilst childhood adversities have been shown to be risk factors for mental, physical, and comorbid health problems in childhood and middle-to-late adulthood, there is less evidence for these associations in early adulthood. It is also unclear if lifestyle factors can modify the risk of these health outcomes following childhood adversities. This study aims to examine childhood adversities as risk factors for psychological distress, obesity, and their comorbidity, and further quantify the moderating impact of lifestyle factors. This could provide insight into potential protective influences against the detrimental health consequences of childhood adversities, particularly mental-physical comorbidity. Methods Analyses were conducted on data from the 1970 British Cohort Study (n = 16,407). The cumulative impact of parent- and self-reported adversities (range: 0–33) were consolidated across childhood (0–16 years) and examined as a predictor of psychological distress (Malaise Inventory ≥ 8), obesity (BMI ≥ 30 kg/m2) and their comorbidity in early adulthood (30 years) using multinomial logistic regression. Self-reported lifestyle factors in adolescence (16 years), including physical activity, diet, sleep duration, smoking, and alcohol consumption were assessed as moderators of the association between childhood adversities and the specified outcome categories. Results A one-item increase on the childhood adversities scale elevated the risk of psychological distress (OR [95% CI]; 1.11 [1.09, 1.13]), obesity (OR [95% CI]; 1.05 [1.03, 1.06]) and mental-physical comorbidity (OR [95% CI]; 1.16 [1.12, 1.20]). Compared to comorbidity, childhood adversity was a weaker risk factor for psychological distress (OR [95% CI]; 0.96 [0.92, 0.99]) or obesity alone (OR [95% CI]; 0.90 [0.87, 0.94]). No lifestyle factors were significant moderators of the association between childhood adversities and these health outcomes. Conclusions Consistent with evidence from middle- to late-adulthood, childhood adversities showed a stronger association with comorbidity in early adulthood than mental or physical health problems alone. There was no evidence that lifestyle factors influenced the association between childhood adversities and comorbidity or individual health problems. Our findings highlight the importance of considering comorbidities when investigating the negative health consequences of childhood adversities, and therefore, the continuing need to identify factors which mitigate the increased risk of comorbidity.